The tombs of Atuan - Le Guin, Ursula K., 1929- (New York : Aladdin Paperbacks, 2001)
Arha's isolated existence as high priestess in the tombs of Atuan is jarred by a thief who seeks a special treasure.
"A Jean Karl Book.".
Booklist, September 2002.
Elem. School Library Collection, June 2000.
Kirkus Review, October 2000.
Library Journal, June 2002.
Notable/Best Books (A.L.A.), December 1998.
Keywords: Fantasy; Ged (Fictitious character) -- Fiction; Magic -- Fiction; Wizards -- Fiction; Ged (Fictional character) -- Fiction; Magic -- Fiction; Wizards -- Fiction; Fantastic fiction